2016
DOI: 10.1016/j.matbio.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical analysis of a lethal laminin alpha-1 mutation reveals altered self-interaction

Abstract: CitationPatel TR, Nikodemus D, Besong TMD, Reuten R, Meier M, et al. (2015) Biophysical analysis of a lethal laminin alpha-1 mutation reveals altered self-interaction. Matrix Biology. AbstractLaminins are key basement membrane molecules that influence several biological activities and are linked to a number of diseases. They are secreted as heterotrimeric proteins consisting of one α, one β, and one γ chain, followed by their assembly into a polymer-like sheet at the basement membrane. Using sedimentation v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…In the developing lens, the capsule is a basement membrane for the attachment of the basal surface of epithelial cells during the synchronized proliferation, migration, and elongation to form layers of transparent lens fibers organized precisely into the optical element of the Zebrafish visual system. As a key component of the basement membrane, laminin is a marker for the lens capsule (Parmigiani and McAvoy, ; Menko et al, ; Norose et al, ; Yan et al, ; Lee and Gross, ; Danysh and Duncan, ; Kwan, ; James et al, ; Patel et al, ). Laminin mutants disrupt basement membrane structure, resulting in abnormal lens development in Zebrafish as early as 3 dpf, with some mutations causing complete loss of the lens as early at 7 dpf (Parmigiani and McAvoy, ; Semina et al, ; Zinkevich et al, ; Pathania et al, ; Patel et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the developing lens, the capsule is a basement membrane for the attachment of the basal surface of epithelial cells during the synchronized proliferation, migration, and elongation to form layers of transparent lens fibers organized precisely into the optical element of the Zebrafish visual system. As a key component of the basement membrane, laminin is a marker for the lens capsule (Parmigiani and McAvoy, ; Menko et al, ; Norose et al, ; Yan et al, ; Lee and Gross, ; Danysh and Duncan, ; Kwan, ; James et al, ; Patel et al, ). Laminin mutants disrupt basement membrane structure, resulting in abnormal lens development in Zebrafish as early as 3 dpf, with some mutations causing complete loss of the lens as early at 7 dpf (Parmigiani and McAvoy, ; Semina et al, ; Zinkevich et al, ; Pathania et al, ; Patel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As a key component of the basement membrane, laminin is a marker for the lens capsule (Parmigiani and McAvoy, ; Menko et al, ; Norose et al, ; Yan et al, ; Lee and Gross, ; Danysh and Duncan, ; Kwan, ; James et al, ; Patel et al, ). Laminin mutants disrupt basement membrane structure, resulting in abnormal lens development in Zebrafish as early as 3 dpf, with some mutations causing complete loss of the lens as early at 7 dpf (Parmigiani and McAvoy, ; Semina et al, ; Zinkevich et al, ; Pathania et al, ; Patel et al, ). The involvement of laminin in the formation of the basement membrane was the basis for using laminin antibodies to label the lens capsule in wt and occ eyes (Pathania et al, ; Pathania et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodologies and interpretations of experimental data that were developed by him and his many collaborators continue to be applied to a wide range of problems of biological and medical significance, especially in the field of protein-protein interactions. A multitude of structure-function studies, recently ranging from the molecular basis of murine olefaction (Portman et al 2014), through the heterodimeric character of a plant immune receptor (Williams et al 2014), to a lethal mutation in the laminin alpha-1 gene (Patel et al 2015), has demonstrated the importance of the thermodynamic approach to significant molecular biological problems. It can only be anticipated that the influence of Don's work and its application will still be felt many decades into the future.…”
Section: Resultsmentioning
confidence: 99%
“…SEC-purified samples were subjected to 0.1 mm filtration before equilibrating at 20 C for 5 min for DLS analysis. The hydrodynamic radius (R h ) distributions were obtained using a Nano-S Zetasizer (Malvern, Toronto, ON, Canada) at concentrations between 1 and 10 mg/mL as described previously (29)(30)(31). SV experiments were performed as previously described (30,32)…”
Section: Hydrodynamic Characterizationmentioning
confidence: 99%